Effect of dietary betaine supplementation on the performance, carcass yield, and intestinal morphometrics of broilers submitted to heat stress - Sakomura, N. K. [UNESP]; Barbosa, N. A A [UNESP]; Longo, F. A.; da Silva, E. P.; Bonato, M. A. [UNESP]; Fernandes, J. B K [UNESP] (My University, 2013)
The objective of this study was to evaluate the effect of betaine in methionine- and choline-reduced diets fed to broilers submitted to heat stress. In total, 1,408 male broilers were randomly distributed into eight treatments, according to 2 × 4 (environment x diet) factorial arrangement, with eight replicates of 2 birds each. Birds were reared environmental chambers under controlled temperature (25-26 °C) or cyclic heat-stressing temperature (25-31 °C). The following diets were tested: positive control (PC), formulated to meet broiler nutritional requirements; negative control (NC), with reduced DL-methionine and choline chloride levels; and with two supplementation levels of natural betaine to the negative control diet (NC+NB1 and NC+NB2). Live performance, carcass traits, and intestinal morphometrics were evaluated when broilers were 45 days of age. The results showed that all evaluated parameters were influenced by the interaction between environment and diet, except for breast meat drip loss. The breakdown of the interactions showed that birds fed the PC diet and reared in the controlled environment had greater breast drip loss than those submitted to the cyclic heat-stress environment. Birds submitted to cyclic heat stress and fed the PC diet presented the lowest feed intake. Feed conversion ratio was influenced only by diet. The FCR of broilers fed the NC+NB2 diet was intermediate relative to those fed the PC and NC diets. The addition of betaine in the diet, with 11.18% digestible methionine and 24.73% total choline reductions, did not affect broiler live performance, carcass yield, or intestinal morphometrics.
Keywords: Additives; Environment; Methionine; Temperature